A Spectral, Optical, Microscopic Study, Synthesis and Characterization of PVC Films Containing Schiff Base Complexes (Baghdad Science Journal, 2019)
In this work, synthesis of conducting polymeric films namely, PVC thin films was carried out containing Schiff base (L) with Cu2+, Cr3+, Ni2+, Co2+, in addition to inspecting the possibilities of measuring energy gap values of PVC-L-M with variety metal ions. These new polymeric films (PVC-L-M) were characterized by FTIR spectrophotometry, energy gap and surface morphology. The optical data recorded that the band gap values are influenced by the type of metals. All modified films have a red shift in optical properties in the ultraviolet region. The PVC-L-Co(II) was the lowest value of the optical band gap, 3.1 eV.